2020
DOI: 10.35134/jpsy165.v13i2.20
|View full text |Cite
|
Sign up to set email alerts
|

Studi Komparatif tentang Kemandirian pada Anak Usia Taman Kanak-Kanak Ditinjau dari Ibu Bekerja dan Tidak Bekerja

Abstract: This study aims to determine the differences in independence of kindergarten-aged children in terms of working and nonworking  mothers in the kindergartens over Talawi district, Sawahlunto sity. This research is a type of comparative research. The variable used in this study is independence. The sampling technique uses random sampling where samples from the population were carried out randomly without regard to strata that exists in the population. The sample of this study was 161 kindergarten children consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Dalam hal ini peran ibu, seperti yang dikemukakan oleh Geovanny (2016) berperan penting dalam membentuk kemandirian anak melalui interaksi yang dekat dengan anak. Hasil temuan dalam penelitian ini sejalan dengan hasil penelitian sebelumnya yang dilakukan oleh Buana (2018), dimana Buana menunjukkan bahwa dari 42 responden (52,5%) memiliki keterampilan mandiri dan berstatus sebagai ibu rumah tangga (IRT). Temuan ini juga mendukung pandangan beberapa ahli, termasuk Wiyanı (2014), yang mengemukakan bahwa pekerjaan ibu dapat berpengaruh terhadap tingkat kemandirian anak.…”
Section: Gambaran Stimulasi Dan Kemandirianunclassified
“…Dalam hal ini peran ibu, seperti yang dikemukakan oleh Geovanny (2016) berperan penting dalam membentuk kemandirian anak melalui interaksi yang dekat dengan anak. Hasil temuan dalam penelitian ini sejalan dengan hasil penelitian sebelumnya yang dilakukan oleh Buana (2018), dimana Buana menunjukkan bahwa dari 42 responden (52,5%) memiliki keterampilan mandiri dan berstatus sebagai ibu rumah tangga (IRT). Temuan ini juga mendukung pandangan beberapa ahli, termasuk Wiyanı (2014), yang mengemukakan bahwa pekerjaan ibu dapat berpengaruh terhadap tingkat kemandirian anak.…”
Section: Gambaran Stimulasi Dan Kemandirianunclassified
“…However, the State Civil Service Agency (BKN) discovered that approximately 30% of ASN still needed to complete their work during the implementation of the work-fromhome system due to technological stuttering (17). This situation demonstrates that the quality of human resources is still an issue.…”
Section: Many Community Service Users Have Complained About Delays In...mentioning
confidence: 99%
“…Given the COVID-19 pandemic, this momentum should force the bureaucracy to accelerate its digital transformation. On the other hand, the State Civil Service Agency (BKN) found that around 30 percent of ASNs did not perform their duties during the work-from-home period due to technological issues (Jannah, 2022). This condition indicates the ongoing problems related to the quality of human resources.…”
Section: Public Service In the Pandemic Eramentioning
confidence: 99%